Metal-organic frameworks (MOFs) as fluorescence sensors: principles, development and prospects - Wu, Tingting; Gao, Xiang-jing; Ge, Fayuan; Zheng, He-gen (CrystEngComm, 2022)
MOFs are self-assembled by inorganic metals and organic ligands, which have the advantages of inorganic and organic materials. With their porosity, chemical tunability and moderate-to-high stability, MOFs have become excellent candidates for fluorescent sensors. The accuracy, sensitivity, selectivity and linear range of the MOF-based fluorescence sensor can be further improved by introducing other fluorescent molecules into the MOFs. MOF-based fluorescence sensors can be widely used in water and air pollution detection, early diagnosis and treatment of diseases and other fields. This review focuses on the principles of MOF-based fluorescence sensors, including the origin of the fluorescence signal, response mode and mechanism. The latest developments in MOF-based fluorescence sensors are reported according to the classification of the analytes. The challenges faced by MOF-based fluorescence sensors are also discussed and some solutions and directions for the future are proposed. This review classifies the latest developments of MOF-based fluorescence sensors according to the analytes, and discusses the challenges faced by MOF-based fluorescence sensors and promotes some directions for future research.